Chemically induced phenotypes during the blood stage development of Plasmodium falciparum as indicators of the drug mode of action - Reghunandanan, Keerthy; Chandramohanadas, Rajesh (Frontiers in Drug Discovery, 2022)
Malaria remains a health and economic burden, particularly to the marginalized populations around the world. Currently, combating malaria relies on the elimination of mosquito vectors, use of insecticide treated nets and other management policies or through small molecule drugs to perturb the intra-erythrocytic development of the parasite. However, resistance building against commonly used drugs, such as Artemisinin and combinations thereof, have become a concern recently necessitating the identification of novel pharmacophores with unique mechanisms of action. This review summarizes various life-stage events of the malaria parasite, Plasmodium falciparum, during the in vitro development that can be targeted by different classes of small molecules. We also describe various chemically induced phenotypes and methods to ascertain and validate such drug-induced changes, as a way to derive early insights into the cellular mechanisms affected.